MISHEMT’s multiple conduction channels influence on its DC parameters - Canales, Bruno G. [UNESP]; Agopian, Paula G. D. [UNESP] (Journal of Integrated Circuits and Systems, 2023)
The Si3N4/AlGaN/AlN/GaN Metal-Insulator-Semiconductor High Electron Mobility Transistor (MISHEMT) analog performance was ascertained considering the device’s multiple channels. MISHEMTs with different gate lengths, source/drain electrodes depths, source/drain distances to the gate electrode and AlGaN aluminum molar fractions were analyzed. The total drain current has 3 different components, where one of them is related to MOS conduction and the other two are related to HEMT conduction. Due to their different transport mechanism and distance to the gate electrode, each channel conduction exhibits different threshold voltages, causing unusual transfer and output characteristics, such as transconductance multiple slopes and a steady output resistance. As a result, the MISHEMTs presents an unexpected increase in intrinsic voltage gain (Av) for high gate bias (strong conduction). The HEMT conduction and the conduction through all the AlGaN volume are responsible for sustaining drain current levels so high that it affects the Early voltage more strongly than the degradation of output conductance, ensuring a high Av values.
Keywords: AlGaN; AlN; Analog Parameters; GaN; Intrinsic Voltage Gain; Multiple Channel; —MISHEMT